A Comparative Evaluation of Smear Layer Removal Using Erbium:YAG Laser-Activated Irrigation, Sonic Irrigation, and Manual Dynamic Irrigation: A Scanning Electron Microscope Study: Comparative Evaluation of Smear Layer Removal - Thapak, Gourav; Arya, Ashtha; Grewal, Mandeep S.; Arora, Anshul (Journal of Lasers in Medical Sciences, 2021)
Introduction: The conventional chemomechanical procedures are ineffective incomplete disinfection of the pulp space due to the complexities of the root canal architecture. The present study aims to compare the efficacy of erbium: YAG laser-activated irrigation, sonic irrigation, and manual dynamic irrigation in the removal of the smear layer through a scanning electron microscope study. Methods: Fifty extracted single-rooted mandibular premolars with a single canal were used and instrumented until F3 ProTaper rotary file reached the working length. Upon the completion of the canal preparation, each specimen was irrigated with 3 mL of 4% NaOCl for 3 minutes, 3 mL saline for 1 minute, and 3 mL of 17% EDTA for 3 minutes. The teeth were assigned to three experimental groups (n=15 each): manual dynamic irrigation, sonic irrigation (EndoActivator), and Er: YAG laser using an X pulse tip. Root canals were sectioned longitudinally and the smear layer at the apical, middle, and coronal third was examined under a scanning electron microscope. Smear layer scores were analyzed by Kruskal-Wallis and Mann-Whitney U tests at P=0.05. Results: The Er: YAG laser group showed significantly lower smear layer scores in the apical third as compared to all other groups. EndoActivator resulted in better cleaning efficacy at the apical area compared to manual dynamic agitation. Conclusion: This study showed results in favor of Er:YAG with an X-pulse tip followed by EndoActivator activation. DOI: 10.34172/jlms.2021.22